2017
DOI: 10.31234/osf.io/gm8qv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personality and Social Relationships: As Thick as Thieves

Abstract: This chapter shows that personality traits and social relationships are deeply entwined in a bidirectional way: Individuals select relationships partly based on their personality traits but at the same time develop across the lifespan partly in response to changes in their social environment. Life transitions are an important catalyst of changes in personality-relationship transactions. We argue that personality traits and social relationships are so closely tied that, in our view, the link between personality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…Many leisure activities have a social component (Karp et al, 2006). The majority of research investigating the role of social engagement in personality development has focused on social network size (e.g., Lang et al, 1998;Mund et al, 2018) or social role status (e.g., Lodi-Smith & Roberts, 2012) but less on leisure behavior. Up to now, research on the relationship between personality and leisure activity has been rare.…”
Section: What Personality-leisure Activity Transactions Can We Expect?mentioning
confidence: 99%
“…Many leisure activities have a social component (Karp et al, 2006). The majority of research investigating the role of social engagement in personality development has focused on social network size (e.g., Lang et al, 1998;Mund et al, 2018) or social role status (e.g., Lodi-Smith & Roberts, 2012) but less on leisure behavior. Up to now, research on the relationship between personality and leisure activity has been rare.…”
Section: What Personality-leisure Activity Transactions Can We Expect?mentioning
confidence: 99%
“…Cornwell, 2014), even if in the long term more peripheral ties are lost (as one reviewer noted). Finally, personality plays a role, particularly as extroverts are especially likely to get and keep ties (Asendorpf and Wipers, 1998;Mund, et al, 2018;Sasovova et al, 2010;Zhu et al, 2013).…”
Section: Which Egos Are Likeliest To Keep Ties or Drop Ties?mentioning
confidence: 99%
“…the first romantic relationship or birth of a child) and work (e.g. the first job) have great potential to stimulate personality socialization (Bleidorn et al, ; Denissen, Luhmann, Chung, & Bleidorn, ; Jokela, Kivimaki, Elovainio, & Keltikangas‐Jarvinen, ; Neyer & Asendorpf, ; Neyer & Lehnart, ; Scollon & Diener, ; van Scheppingen et al, ; Wagner, Becker, Lüdtke, & Trautwein, ; for a review, see Mund, Jeronimus, & Neyer, ). For instance, in the love and family domain, research has repeatedly shown that finding a partner is associated with decreases in Neuroticism and related traits, increases in Extraversion, and increases in Conscientiousness (Lehnart et al, ; Neyer & Asendorpf, ; Neyer & Lehnart, ; Wagner et al, ).…”
Section: Personality Development In Early Adulthoodmentioning
confidence: 99%